Community Movement and Communication for Anticipation of Volcanic Eruption and Covid 19 - Rudy Handoko (Universitas Multimedia Nusantara, 2022)
For many years, people are finding ways in anticipating disasters such as volcanic eruptions that happen frequently in Merapi area. Many early warning systems had been installed; however, casualties still took place. This study examined the community's expectations of and responses to disasters, considering the resilience of people in the affected area. Through this research, researcher would like to know how Merapi slope community communicates and anticipates disasters in better way than in the past. The paper analyzes the concept of online and offline communities and the Social Construction of Technology (SCOT) while summarizing recent applications in theory and practice of community movement and communication. The research results showed that this community movement for evacuating refugees spread fast because it was supported by the strong local cultural-based values and social construction in communication technology. This local values also helps significantly during Covid-19 pandemic in 2020. Although the communication within an online community acted as an accelerator, the combination of online and offline communities created a much more responsive, coordinated, and durable social movement. From the theory perspective, the local community engaged in the social construction of technology in using tools for disaster management. A qualitative ethnography approach was used as a research method, and data were collected using in-depth interviews and participatory observation.